A comparison of the three universal set top boxes and the DVB-T2 set top box assembly's signal reception quality - C. Ciksadan; Ade Silvia Handayani; Wildan Putra Pratama (VOLT : Jurnal Ilmiah Pendidikan Teknik Elektro, 2023)
In order to improve the assembled set top box's signal reception sensitivity and compare the signal reception quality with set top boxes from the Sharp, D'Color, and HDTV brands, this study will design a set top box with an LNA on the receiver side. Using a Spectrum Analyzer tool to view the RSSI (Receive Signal Strength Indicator) value of each set top box as a signal reception quality parameter, data from each set top box used in four different locations in Palembang City—Kenten, Plaju, Kamboja, and Bukit—were collected for this study. The assembled set top box's RSSI value was higher than that of other set top boxes, which indicated that its signal reception quality was better to that of other set top boxes, according to the measurement results at four research locations. This indicates that the LNA applied to the built set top box device can improve the sensitivity of the reception quality of the signal received. In comparison to other areas, Kamboja has the best signal reception because it is nearest to the TV transmitter tower.